Changing the way we train surgeons in the 21th century: A narrative comparative review focused on box trainers and virtual reality simulators. (April 2019) - Papanikolaou, I.G.; Haidopoulos, D.; Paschopoulos, M.; Chatzipapas, I.; Loutradis, D.; Vlahos, N.F.
Abstract: The traditional method of acquiring surgical skills by observing and assisting in surgical procedures involving human beings has been challenged during the past several years. Lessons obtained from aviation suggested that the use of simulators is related to reduced costs, increased efficiency in performing certain tasks and above all safety. A shift in paradigm is also required in modern surgical training. The development of endoscopic surgery allowed for the incorporation of medical simulators into training programmes. A review of the literature was conducted using specific inclusion and exclusion criteria, for articles published up to July 31th, 2018. Relevant studies were identified using computerized bibliographic searches of MEDLINE database. The keywords that were used in various combinations were: "Medical Simulators", "Surgical Training", "Laparoscopy", "Surgical Skills", "Box trainers", "Virtual reality simulators", "Surgical Education". Surgical training with box trainers and/or virtual reality simulators confers a significant benefit in terms of surgical skills development, increases patient safety and reduces costs. Nevertheless, the use of virtual reality simulators was significantly more expensive. Simulation training allows trainees to learn from their mistakes, to repeat surgical tasks multiple times so as to establish muscle memory, and enhance skill competency with the aid of informative feedback. Simulators are necessary for the development of the skills required to meet the specific needs of endoscopic surgery in the 21st century. Teaching hospitals should introduce simulation training programmes in order to increase efficiency, reduce costs and improve patient safety. As medical advancements continue to transform the way we perform surgery day by day, simulation training will play a pivotal role in every surgical specialty.